Divorce and Loss: Helping Adults and Children Mourn When a Marriage Comes Apart - Ehrlich, Joshua (Rowman & Littlefield Publishers, 2014)
Divorce and Loss: Helping Adults and Children Mourn When a Marriage Comes Apart places loss and mourning at the center of the divorce experience and details how therapists can facilitate mourning through individual therapy and through interventions with parents. The book offers detailed clinical vignettes to illuminate family members’ reactions to divorce and to highlight interventions. Ehrlich also explores how failures of mourning in response to divorce create difficulties for people, including bitter, high-conflict divorces. He examines how therapists can intervene more effectively with difficult divorces and avoid ethical and clinical pitfalls. In addition, the book examines the very strong feelings that divorce elicits in therapists and how to deal with these constructively.